Recruitment and Retention of Pregnant and Breastfeeding Mothers for Longitudinal Clinical Microbiome Studies (OR30-08-19). (13th June 2019) - Lemas, Dominick; Wright, Lauren; Francois, Magda; Chen, Lynn; Hentschel, Austen; Schleffer, Andrew; Chen, Huan; Flood-Grady, Elizabeth; Neu, Josef; Shenkman, Elizabeth; Krieger, Janice
Abstract: Objectives: Accumulating data suggest the health benefits of breastfeeding are, in part, mediated through interactions with the human microbiome. Despite these observations, recruitment of pregnant mothers in longitudinal clinical microbiome studies remains a significant challenge. The goal of this study is to develop data-driven strategies for recruitment and retention of breastfeeding mothers' into longitudinal clinical microbiome studies. Methods: We recruited a total of 40 mothers (20 pregnant and 20 breastfeeding) to complete in-depth semi-structured interviews at the UF Clinical and Translational Science Institute. Additionally, mothers were asked to use self-administered microbiome collection kits and complete questionnaires related to health history, infant feeding practices, and physical activity. Informative interviews were designed to identify women's understanding, motivations and barriers surrounding longitudinal clinical research participation and their preferences for providing non-invasive biological samples. Results: Our preliminary analysis indicates that 1) barriers for participating in research include convenience, confidentiality and child protection; 2) factors motivating participation in research include general interest in breastfeeding, schedule, and perceived research relevance; 3) participant recruitment should consider social media and 4) biological sample collection should include adequate instructions and drop-off convenience. Conclusions: The results of this study provide valuable theoretical and practical insights on how to effectively recruit and retain pregnant and breastfeeding women into longitudinal microbiome studies. Funding Sources: 1K01DK115632-01A1.